2019
DOI: 10.21037/atm.2019.03.66
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sub-chronic, low-dose cadmium exposure on kidney damage and potential mechanisms

Abstract: Background: The present study was to investigate the potential mechanisms underlying the sub-chronic low-dose cadmium (Cd) exposure induced renal injury in rats.Methods: Totally 40 male adult SD rats were randomly divided into four groups: control group, low-dose Cd group (1 mg/kg CdCl 2 ), moderate-dose Cd group (2.5 mg/kg) and high-dose Cd group (5 mg/kg).Results: From the 3 rd week, the body weight of rats in moderate-dose and high-dose declined significantly as compared to the control group (P<0.05); the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Once inside the mitochondria, cadmium can bind thiol-containing proteins and impair the corresponding protein function [ 80 ]. Studies have demonstrated that upon exposure to cadmium, kidney mitochondria displayed deformation, swelling, and vaculation, concurrent with increased SOD1 expression and decreased SOD2 and catalase expression [ 115 ]. Additionally, the anti-apoptotic protein BCL-2 was also found decreased by cadmium exposure [ 115 ]; so was the ratio between reduced glutathione and oxidized glutathione [ 60 ].…”
Section: Effects Of Cadmium On Mitochondrial Functionmentioning
confidence: 99%
“…Once inside the mitochondria, cadmium can bind thiol-containing proteins and impair the corresponding protein function [ 80 ]. Studies have demonstrated that upon exposure to cadmium, kidney mitochondria displayed deformation, swelling, and vaculation, concurrent with increased SOD1 expression and decreased SOD2 and catalase expression [ 115 ]. Additionally, the anti-apoptotic protein BCL-2 was also found decreased by cadmium exposure [ 115 ]; so was the ratio between reduced glutathione and oxidized glutathione [ 60 ].…”
Section: Effects Of Cadmium On Mitochondrial Functionmentioning
confidence: 99%
“…Moreover, another potential mechanism by which Cd may decrease the activity of antioxidant enzymes is an interaction with divalent elements, such as manganese, zinc, and selenium; these elements function as cofactors and form the core active sites of antioxidant enzymes (e.g., superoxide dismutase, catalase, and glutathione reductase) (Cuypers et al, 2010;Matović et al, 2015). After chronic exposure to low-dose Cd, nephrotoxicity occurs with increased renal ROS level and decreased activity of antioxidant enzymes (Wang et al, 2013;Ansari et al, 2017;Liu et al, 2019). However, oxidative stress is a dynamic equilibrium process; there is an adaptive system to eliminate ROS, and oxidative damage would appear only when ROS was overloaded.…”
Section: Ke1: Oxidative Stressmentioning
confidence: 99%
“…The epithelial cells in the glomeruli of the renal glomeruli and the absence of urinary space in the Bowman capsule enlarge due to the large capillary expansion (31). The glomeruli swell, the renal tubules narrow, the epithelial cells in the renal tubules die, accumulate in the cavities, infiltration of inflammatory cells and edema (18). Congestion and inflammation around the blood vessels, fibrosis of the tissue and condensed nuclei in the cells of the renal tubules (28).…”
Section: Cadmium Toxicity In Kidneysmentioning
confidence: 99%
“…However, the initial stages of cadmium-induced proximal tubule damage may include many specific changes in cellular signaling pathway, cellular adhesions, and autophagy that happen before the onset of necrotic or apoptotic mechanisms (49). Cadmium may cause renal damage according to the method of giving, which may be ascribed to the disordered absorption of iron ions, disruption of oxidative stress and apoptosis in the kidney (18).…”
Section: Cadmium Toxicity In Kidneysmentioning
confidence: 99%
See 1 more Smart Citation